GAYA HIDUP MEROKOK, MINUM KOPI, POLA ISTIRAHAT DAN TEKANAN DARAH PADA DEWASA MUDA DI PETRIKORA - Sheylla Tara Audina; Putu Suiraoka; IGA Ari Widarti (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2021)
Based on Health Profile of Badung Regency on 2018, the prevalence of people with hypertension that received health care are 76,7% of the total population. The objective of this research is to find out the blood pressure based on the life style from adults. Observational method is used on this research, by using comparation from 30 samples. There are 2 types of data used, primary and secondary data. The method of collecting data is through interview, questionnaire and recording. The samples which have behavior of drinking coffee (66.67%) and the samples which do not drinking coffee (33.33%). The samples which have behavior of smoking (56.67%) and the samples who do not smoke (43.33%). Samples that have the behavior of drinking coffee have high blood pressure on average 140/80 mmHg, samples that have behavior of smoking have high blood pressure on average 140/80 mmHg, and samples that have poor rest patterns have high blood pressure on average 140/80 mmHg. In this case, for the visitor who have certain life style such as the behavior of drinking coffee, staying up late and smoking, are expected to apply healthy life style for maintaining health.Keywords : blood pressure, coffee, smoking, rest patterns